Study guides

Q: How do you solve y plus 1 divided by 3 equals 2?

Write your answer...

Submit

Related questions

1

1*1*1*1*1+1=4 divided by4

Y equals 1 and X equals 1

-1 plus 1 = 0 plus 1 =1

1.66666666666666666667 because 3 plus 1 plus 1 equals 5 and 5 divided by 3 equals 1.6666666666666666666.7.

4/x - 1 + 6/3x +1 = 15/3x + 1 4/x - 1 + 2/x +1 = 5/x + 1 4/x + 2/x - 5/x = 1 + 1 -1 1/x = 1 x = 1

x = 5, y = -1

i have no clue what the answer is

x equals subtract 11 divided by 3

9 divided by 9 equals 1, and 3 times 12 equals 36. 1 plus 36 equals 37.

-1

Your equations are not worded properly.

A = 1, B = 9

2 plus 1-x divided by.

It depends if 1 plus tan theta is divided or multiplied by 1 minus tan theta.

3 divided by 4 plus 1 divided by 2 minus 2 divided by 3

1

wel i cant explain how i did this but the answer is -1/7

It equals 2 over 8.

a+a=1 2a=1 a=1/2

No. In the order of operations, 5 divided by 5 comes first. Let's say x equals 2. 2 plus 5 divided by 5 plus two 2 plus 1 plus 2 3 plus 2 equals 5. The answer is 5

That factors to (a + 1)(a + b) a = -1, -b b = -a

If: x+1+2x = 1x+5 Then: x = 2

1.00000000075

85